Eddy Kinetic Energy in the Arctic Ocean From a Global Simulation With a 1-km Arctic - Wang, Qiang; Koldunov, Nikolay V.; Danilov, Sergey; Sidorenko, Dmitry; Wekerle, Claudia; Scholz, Patrick; Bashmachnikov, Igor L.; Jung, Thomas (Geophysical Research Letters, 2020)
Simulating Arctic Ocean mesoscale eddies in ocean circulation models presents a great challenge because of their small size. This study employs an unstructured-mesh ocean-sea ice model to conduct a decadal-scale global simulation with a 1-km Arctic. It provides a basinwide overview of Arctic eddy energetics. Increasing model resolution from 4 to 1 km increases Arctic eddy kinetic energy (EKE) and total kinetic energy (TKE) by about 40% and 15%, respectively. EKE is the highest along main currents over topography slopes, where strong conversion from available potential energy to EKE takes place. It is high in halocline with a maximum typically centered in the depth range of 70–110 m, and in the Atlantic Water layer of the Eurasian Basin as well. The seasonal variability of EKE along the continental slopes of southern Canada and eastern Eurasian basins is similar, stronger in fall and weaker in spring.